Pengaruh Inovasi Produk, Live Streaming Shopping, dan Influencer Marketing Terhadap Minat Beli Online Produk Bittersweet By Najla Pada Generasi Z di Kabupaten Bekasi - Basar Maringan Hutauruk; Suryadi Suryadi (Jurnal Fokus Manajemen, 2026)
This study is motivated by the increasing competition in the culinary business, which requires creative marketing strategies to attract consumers, especially Generation Z who are highly engaged with digital technology. The objective of this research is to analyze the influence of product innovation, live streaming shopping, and influencer marketing on online purchase intention of Bittersweet by Najla products in Bekasi Regency. This research employed a quantitative approach with independent variables consisting of product innovation, live streaming shopping, and influencer marketing, while the dependent variable was online purchase intention. Data were collected through questionnaires distributed to 100 Generation Z respondents in Bekasi Regency using purposive sampling. The data were analyzed using multiple linear regression. The results indicate that product innovation and live streaming shopping positively affect online purchase intention, while influencer marketing shows a negative effect. Simultaneously, the three variables significantly influence online purchase intention. These findings imply that companies should focus more on product development and interactive live streaming strategies, while being more selective in choosing influencers who align with the target market.The originality of this study lies in the simultaneous integration of three digital marketing variables within the context of a viral culinary brand in Indonesia, with a specific focus on Generation Z as a strategic market segment.